2014
DOI: 10.1167/iovs.13-13510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor in Human Ocular Adnexal Lymphoma

Abstract: This study demonstrated increased VEGF expression in human conjunctival and orbital EMZL compared with that in RLH, suggesting that VEGF plays a significant role in the pathogenesis and tumor angiogenesis of ocular adnexal lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Intratumoral microvessel density was calculated according to the previous reports. 8 , 9 Briefly, the number of CD34-immunopositive microvessels in the tumor tissues was directly counted under light microscope (objective ×40). The counting was done in two or three high-power fields, and the numbers were then averaged to determine the microvessel density.…”
Section: Methodsmentioning
confidence: 99%
“…Intratumoral microvessel density was calculated according to the previous reports. 8 , 9 Briefly, the number of CD34-immunopositive microvessels in the tumor tissues was directly counted under light microscope (objective ×40). The counting was done in two or three high-power fields, and the numbers were then averaged to determine the microvessel density.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF expression may be strongly correlated with pathological characteristics of diffuse large B cell lymphoma (DLBCL) [41]. VEGF plays a significant role in the pathogenesis and tumor angiogenesis of ocular adnexal lymphoma [42]. Both VEGFR-2 and VEGFR-3 can serve as markers for prognosis of papillary renal cell carcinoma.…”
Section: Non-digestive Cancersmentioning
confidence: 99%
“…IgG4-ROD simulates B-cell malignant lymphomas such as extra nodal marginal zone B-cell lymphoma (EMZL) (2,3), and the differentiation is sometimes difficult based on histopathological examination only. In addition, we have shown that CD20 and vascular endothelial growth factorimmunopositive B lymphoid cells were detected in tumor tissues of both ocular adnexal EMZL and benign reactive lymphoid hyperplasia (4). Therefore, further information should be collected to differentiate benign lymphoproliferative disorders from EMZL for ophthalmologists.…”
mentioning
confidence: 99%